PEMAKNAAN ILUSTRASI JOKO WIDODO DALAM KASUS PEMECATAN ANGGOTA KPK PADA SAMPUL KORAN TEMPO : (ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study examines the illustrations in Tempo newspaper September 17, 2021 edition, September 18 2021 edition, September 20 2021 edition, and September 30 2021 edition. This study aims to determine the message contained in an illustration which is generally used as an alternative to convey messages and attract attention. The reader uses the semiotic analysis theory from Roland Barthes which divides it into three stages in interpreting a sign, namely denotation, connotation, and myth. The meaning of denotation, connotation, and myth is interpreted by researchers based on sight, observation, knowledge, and others. The freedom for researchers to express and interpret the meaning of a photo is a feature and theory of semiotics. The results of the study show that the four illustrations serve as a critique of Jokowi's response to the case of the dismissal of 56 KPK members which was delivered in satire. The illustration illustrates Jokowi's response to the decision to dismiss dozens of members who did not pass the National Insight Test (TWK) until the day of dismissal. The overall meaning of the four illustrations is that Jokowi as head of government is required to cancel the dismissal of 56 KPK members who did not pass the TWK because in practice there are many irregularities to discrimination. In the end, Jokowi gave a solution by offering the dismissed members to join the National Police Chief. The representation of Joko Widodo's figure based on the meaning of denotation, connotation, and myth that has been classified by researchers sees that Joko Widodo is described as inconsistent and more confused in making decisions about KPK members who will be fired.